The Interplay of Product Innovation, Technological Adaptation, and Customer Perception in Driving Competitive Advantage: Insights from the Creative Industry - Masruchan Masruchan (Takaza Innovatix Labs Ltd., 2025)
Abstract: This study examines the impact of Product Innovation on Competitive Advantage in the creative industry, with a focus on the mediating roles of Technological Adaptation, Customer Perception of Innovation, and Market Responsiveness. Employing a quantitative research design, data were collected from 100 chatbot users in content creator communities on TikTok, Instagram, and Facebook. The analysis, conducted using Smart PLS, reveals that product innovation significantly enhances competitive advantage, both directly and indirectly through technological adaptation and customer perception of innovation. Notably, technological adaptation demonstrates the strongest mediation effect, emphasizing the importance of technological integration in leveraging innovation for competitive outcomes. Conversely, market responsiveness shows a moderate mediating effect, suggesting its context-dependent role in driving competitiveness. A negative relationship between technological adaptation and competitive advantage underscores the risks associated with misaligned technology strategies. These findings contribute to the literature on innovation management by providing empirical insights into the interplay of innovation, technology, and customer engagement in achieving sustainable competitive advantage. The study recommends that organizations adopt a holistic approach to innovation, balancing technological advancements and customer-centric strategies. Future research should investigate longitudinal effects, industry-specific variations, and the influence of organizational culture on these dynamics.